Daily oral intake of β-cryptoxanthin ameliorates neuropathic pain. Issue 5 (4th May 2017) - Park, Gyujin; Horie, Tetsuhiro; Iezaki, Takashi; Okamoto, Maika; Fukasawa, Kazuya; Kanayama, Takashi; Ozaki, Kakeru; Onishi, Yuki; Sugiura, Minoru; Hinoi, Eiichi
Abstract: β-cryptoxanthin, a xanthophyll carotenoid, exerts preventive effects on various lifestyle-related diseases. Here, we found that daily oral administration of β-cryptoxanthin significantly ameliorated the development of tactile allodynia following spinal nerve injury but was ineffective in mechanical allodynia in an inflammatory pain model in mice. Our results suggest that β-cryptoxanthin supplementation would be beneficial for the prophylaxis of neuropathic pain.